Decreasing ALT donor site morbidity with the keystone flap. Issue 6 (9th March 2018) - Turin, Sergey Y.; Spitz, Jamie A.; Alexander, Karina; Ellis, Marco F.
Abstract : Background: The anterolateral thigh (ALT) flap is a workhorse flap for a variety of wounds. The primary disadvantage of ALT flaps is donor site morbidity associated with large skin paddle defects. We present a strategy of managing the donor site with the Keystone flap to avoid skin grafts in cases where primary closure is not possible. Methods: A retrospective, multi‐institutional review from December 2015 to March 2017 based on a single surgeon's experience was performed. Inclusion criteria were harvest of an ALT flap and closure of the thigh donor site with a keystone flap. Results: Six patients underwent reconstruction of the ALT donor site with a keystone flap. The average width of the ALT skin paddle was 7.8 cm (range 7–8 cm) and the defects could not be closed primarily or with wide undermining. Surface area of the ALT flaps averaged 96.8 cm 2 (range 64–152 cm 2 ). Mean patient BMI was 24.6 (range 16–37). Keystone flap dimensions averaged 9.5 × 17.8 cm. There were no major donor or recipient site complications, and one ×minor complication of delayed wound healing. No patients exhibited decreased range of motion at the hip or knee. Conclusions: Primary closure of the ALT donor site is preferred, but becomes difficult as skin paddle width approaches 8 cm. Managing the ALT flap donor site with a keystone flap is safe, does not appear to have significant morbidity, and can allow the surgeon to avoid the morbidity and secondary donor site associated with skin grafting.